Pemberdayaan Pekerja Migran Perempuan Indonesia di Hong Kong melalui Pelatihan Manajemen Stres, Penetapan Tujuan, dan Kewirausahaan Berbasis Participatory Action Research : Empowering Indonesian Female Migrant Workers in Hong Kong through Integrated PAR-Based Training - S. Sriyanto (Universitas Muhammadiyah Purwokerto, 2026)
Indonesian female migrant workers in Hong Kong face complex psychological challenges due to their dual roles as breadwinners abroad and family caretakers in their home country. This dual burden often leads to stress, work–family conflict, and a lack of future orientation after returning home. This community service program aimed to enhance stress management skills, goal setting, and economic independence through an integrated training based on Participatory Action Research (PAR). The program involved 33 female migrant workers from Indonesian community groups in Hong Kong. The activities consisted of three main components: (1) stress management training based on psychoeducation and Islamic approaches, (2) goal-setting training using SMART principles, and (3) basic entrepreneurship training. Evaluation was conducted using a pre-test and a post-test to measure changes in stress levels, understanding, and stress management abilities. The results indicated a significant decrease in stress levels and improvement in participants’ understanding and coping skills after the training. Furthermore, participants demonstrated higher motivation to plan for the future and to develop small-scale entrepreneurial initiatives. These findings highlight that the PAR-based training effectively strengthens psychological resilience, self-reliance, and emotional well-being among female migrant workers. This model is recommended for replication and sustainable implementation to empower Indonesian migrant worker communities abroad.